2021
DOI: 10.26434/chemrxiv-2021-j18mg-v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel Pyrazolo[3,4-c]pyridine Antagonists with Nanomolar affinity for A1 / A3 Adenosine Receptors: Binding Kinetics and Exploration of their Binding Profile Using Mutagenesis Experiments, MD simulations and TI/MD calculations

Abstract: Drugs targeting the four adenosine receptor (AR) subtypes can provide “soft" treatment of various significant diseases. Even for the two experimentally resolved AR subtypes the description of the orthosteric binding area and structure-activity relationships of ligands remains a demanding task due to the high similar amino acids sequence but also the broadness and flexibility of the ARs binding area. The identification of new pharmacophoric moieties and nanomolar leads and the exploration of their binding area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 99 publications
0
6
2
Order By: Relevance
“…The biggest effect in this study was observed for the Y271 7.46 A A 1 R mutation, which caused a ∼10-fold reduction in the binding affinity of 10b ( Table 2 ). This effect is in contrast to that observed previously for pyrazolo[3,4- c ]pyridines 14 for which we showed that the Y271 7.46 A mutation caused a slight increase in binding affinity. Since the MD simulations showed contacts with H278 7.43 and not Y271 7.46 , the Y271 7.46 A mutation in A 1 R might affect the binding of 10b through contact with H278 7.43 .…”
Section: Simulationscontrasting
confidence: 99%
See 4 more Smart Citations
“…The biggest effect in this study was observed for the Y271 7.46 A A 1 R mutation, which caused a ∼10-fold reduction in the binding affinity of 10b ( Table 2 ). This effect is in contrast to that observed previously for pyrazolo[3,4- c ]pyridines 14 for which we showed that the Y271 7.46 A mutation caused a slight increase in binding affinity. Since the MD simulations showed contacts with H278 7.43 and not Y271 7.46 , the Y271 7.46 A mutation in A 1 R might affect the binding of 10b through contact with H278 7.43 .…”
Section: Simulationscontrasting
confidence: 99%
“…This contrasts with our studies using 3-phenyl-7-anilinopyrazolo- [3,4-c]pyridines which showed a 1.5-fold decrease in affinity due to the E172 5.30 A mutation. 14 In addition, mutation of H251 6.2 A has been reported to reduce antagonist affinity against A 3 R 20,21 although here it did not have any effect on 10b affinity at A 1 R. Other residues of interest to mutate were T91 3.36 A and S267 7.42 A, which are deep in the orthosteric pocket. Interestingly, we found that mutation to alanine of these residues also did not have a significant effect on the binding affinity of 10b (Table 2).…”
mentioning
confidence: 57%
See 3 more Smart Citations